Innovation of Islamic Religious Education In Forming The Character of State Defense in The Junior High School of Jakarta - Much Mu’alim (CV ODIS, 2022)
The emergence of the National Defense character education curriculum which is always integrated into every subject certainly cannot be separated from various problems. The government's concern for the character of the younger generation, which has indicated mental decline, is the main factor in implementing this curriculum. The sense of nationalism of the younger generation which is increasingly declining is in the main spotlight. The feeling of nationalism which has recently faded has become one of the impacts of the decline in character education for the younger generation to defend the State. The current trend is that the younger generation does not understand the difficulty of seizing independence from the colonialists. One of the essences of human beings as a nation and state is to love their nation and country, because as good citizens, they should not have any reason not to love their nation. The Indonesian people have local wisdom and rich distinctive values that can be used to live as a nation and state. The method used in this research is to use research and development methods. The purpose of this research is to raise the attitude of defending the country by filling it through positive activities which are almost faded and lost among teenagers.